Strategi KBRI Kuala Lumpur dalam Meningkatkan Total Perdagangan Bilateral Indonesia-Malaysia Tahun 2021-2022 - Novianty, Syarifah Afra; Azizah, Nur (Jayapangus Press, 2024)
Indonesian Embassy Kuala Lumpur has a Trade Division to carry out trade duties in Malaysia. The Trade sector is a representation of the Ministry of Trade of the Republic of Indonesia (Kemendag). In 2020 there was a decrease in total bilateral trade between Indonesia and Malaysia compared to 2019. However, in 2021-2022 total trade increased significantly. This is the basis for writing to find out the strategies used to increase total trade between Indonesia and Malaysia in 2021-2022. This paper uses qualitative methods with primary and secondary data through literature with the theory of functional bilateral cooperation and the concept of diplomacy. The findings of the strategies used in 2021-2022 by the trade sector include: (1) Buying Mission; (2) Business Matching; and (3) Export Promotion under the leadership of Trade Attache, Deden Muhammad F.S. The strategies are based on one of the implementing elements of the Ministry of Trade, namely DJPEN. So, this strategy can increase total bilateral trade between Indonesia and Malaysia in 2021-2022 to reach US21.4 billion and US27.5 billion. This also has an impact on increasing Indonesia's trade surplus in a more positive direction with the export value in 2021-2022 gradually reaching US11.97 billion and US15.42 billion. Thus, bilateral trade between the two fulfills one of the parameters of economic prosperity for Indonesia.